Implementation of Ethnopedagogy Through Tabak Educative Traditional Games for Multicultural Value Reinforcement - Emi Tipuk Lestari; Saiful Bahri (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the use of traditional Tabak games to reinforce multicultural values in Public Elementary School 14, Pontianak City. Utilizing a survey method, the research involved the Pontianak community, teachers, and students from the school. Data collection methods included participant observation, comprehensive interviews, and documentation, with data analysis conducted through an interactive approach. The findings reveal that students favor thematic lessons, particularly history education, when taught using traditional Tabak games. This is evidenced by 90.71 percent of students responding positively to questions about this learning method. The traditional Tabak games embody values such as democracy, education, social skills, personality, courage, unity, and morals. Additionally, the implementation of learning based on local wisdom through traditional educational Tabak games showed an 86.79 percent effectiveness in strengthening multicultural values. This approach provides teachers with an alternative method for creating imaginative and enjoyable educational activities suitable for elementary students. It introduces multicultural values through five dimensions of multicultural education: content integration, knowledge construction, prejudice reduction, and the empowerment of school culture and social structures.